STRATEGI PENGELOLAAN KOMUNIKASI CORPORATE SOCIAL RESPONSIBILITY (CSR) PT PERKEBUNAN NUSANTARA V MELALUI PROGRAM KEMITRAAN DALAM PEMBERDAYAAN UMKM DI KABUPATEN KAMPAR - Yulaika, Rahma; Wirman, Welly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The strategy of managing Corporate Social Responsibility (CSR) through a partnership program can be used to empower UMKM (Micro Small and Medium Enterprises) to become a resilient and independent small business. The purpose of this research is to find out the management strategy of PT Perkebunan Nusnatara V partnership program starting from the planning, implementation, organization, monitoring and evaluation of PT Perkebunan Nusantara V Corporate Social Responsibility (CSR) through a partnership program in empowering UMKM in Kampar Regency.Research using qualitative research methods. By using the concepts of management strategies, communication management, communication of Corporate Social Responsibility communication management strategies for Corporate Social Responsibility, and community empowerment. Next data collection techniques consisted of interviews, observation, and documentation. While the data analysis technique uses descriptive analysis according to Huberman and Miles. For data validity checking techniques using triangulation. The results of the research show that in the partnership program planning process, it is conducted with internal meetings and has not yet followed the stages of communication planning. At the stage of organizing the PKBL division divides each of its employees into each beneficiary Regency. At the stage of organizing communication that occurs face to face and utilizing communication media such as whatsapp and line. In the implementation phase of PT Perkebunan Nusantara V Corporate Social Responsibility (CSR) in collaboration with the Kampar District Koprasi Office. In the implementation there are several stages, namely the submission and acceptance of proposals, the implementation of the survey phase, the stage of receiving assistance and training, and the stage of empowering UMKM in Kampar District. Every step taken by PKBL in managing the program contains an element of communication and requires the role of public relations. UMKM empowerment occurs when UMKM feel helped after receiving funding from the partnership program. The monitoring and evaluation phase involves an internal audit team and an external audit team, then reported to the Ministry of BUMN and Directors of PT Perkebunan Nusantara V.Keywords: Communication Management Strategy, PTPN VV CSR Program, Partnership Program